1997
DOI: 10.1002/macp.1997.021980918
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction of supported zirconocene catalysts with alkylaluminium co‐catalysts

Abstract: The interaction of supported metallocene catalysts with methylaluminoxane leads to the desorption of the metallocene compound from the surface of the support and the formation of highly active homogeneous complexes. The catalytic properties of the system and characteristics of polyethylene formed are determined by these species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…However, and most importantly, in the case of the heterogeneous catalysts, the metallocene leaching was dramatically reduced; according to the yields of the polymerizations with the filtrates of the leaching experiments, in the case of catalyst A, no leaching at all was observed, and in the case of catalyst B, leaching was reduced by 97%! These results indicate that pure (or TMA-free) MAO has far less of a role in the metallocene leaching than previously suggested 6 and that the major reason for leaching is the free TMA in MAO. M w ϭ weight-average molecular weight; M n ϭ number-average molecular weight; T m ϭ melting temperature.…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…However, and most importantly, in the case of the heterogeneous catalysts, the metallocene leaching was dramatically reduced; according to the yields of the polymerizations with the filtrates of the leaching experiments, in the case of catalyst A, no leaching at all was observed, and in the case of catalyst B, leaching was reduced by 97%! These results indicate that pure (or TMA-free) MAO has far less of a role in the metallocene leaching than previously suggested 6 and that the major reason for leaching is the free TMA in MAO. M w ϭ weight-average molecular weight; M n ϭ number-average molecular weight; T m ϭ melting temperature.…”
Section: Resultscontrasting
confidence: 65%
“…In addition to binding the metallocene compounds to the support through the active metal center or through an ion-pair interaction with a methylaluminoxane (MAO)-pretreated support 2 (the two most common methods of heterogenization), resistance against leaching has been enhanced by the bonding of the metallocene covalently to the support through a functional group of a cyclic ligand or an ansa ligand. [3][4][5] Catalyst leaching has been reported to take place especially in the presence of the cocatalyst MAO, 6 -8 which, according to Semikolenova and Zakharov, 6 is suspected of destroying the surface metallocene oxy compounds and forming soluble metallocene-MAO complexes. 6 That particular study did not, however, take into account the fact that commercial MAO solutions also contain trimethylaluminum (TMA), the amount of TMA being, for example, 20 -35% of the total aluminum content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Ihm, we refrained from using MAO as coactivator, as MAO is known to leach metallocenes from their support and simultaneously activate them, 18,21,[31][32][33] thus producing polymers with large polydispersities (M w /M n ). It has been shown that trialkylaluminum compounds can also cause metallocenes to desorb from their support.…”
Section: Initial Studiesmentioning
confidence: 96%
“…The possibility of leaching out of loaded complexes was investigated according to the reported method [6]. Catalyst was suspended in a toluene solution of MAO and filtered.…”
mentioning
confidence: 99%